2018
DOI: 10.11604/pamj.2018.29.34.14576
|View full text |Cite
|
Sign up to set email alerts
|

Fistules obstétricales dans la province du Haut-Katanga, République Démocratique du Congo: à propos de 242 cas

Abstract: Les fistules obstétricales constituent un problème majeur de Santé Publique dans les pays pauvres. L’objectif de ce travail est de décrire les aspects épidémiologiques, cliniques et thérapeutiques des fistules obstétricales dans la province du Haut-Katanga, République Démocratique du Congo. L’étude est transversale descriptive, portant sur 242 patientes souffrant de la fistule obstétricale dans la province du Haut-Katanga durant la période allant de Septembre 2009 à Décembre 2013. Les paramètres étudiés étaien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
25
5
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 24 publications
14
25
5
2
Order By: Relevance
“…This could be explained by the fact that women with obstetric fistula had dropped out of school to get married or had an early pregnancy. The same is true of other authors who reported a high number of patients without formal education [2,5,15,22]. This could be explained by the low literacy rate in rural areas where these women live [7].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This could be explained by the fact that women with obstetric fistula had dropped out of school to get married or had an early pregnancy. The same is true of other authors who reported a high number of patients without formal education [2,5,15,22]. This could be explained by the low literacy rate in rural areas where these women live [7].…”
Section: Discussionsupporting
confidence: 73%
“…These patients travel hundreds of kilometers to reach a health center where they arrive with obstructed labor and fistula under development. As shown in several previous studies, deliveries producing fistulas occurred at home in 70.7 to 97.1% [15][16][17][18].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This study that involved 242 patients depicted a gloomy situation about sociodemographic and obstetrical characteristics of these patients at the time of fistula: 40.1% aged <20, 90.6% of nulliparae, 94.6% of vaginal delivery; 85.9% of ≥48 hours labour duration, 70.7% of home-birth practice, 93.4% of neonatal mortality, and 71.5% of patients living alone. Clinical parameters related to fistula were as follows: a history of fistula of 5 years and more (33.5%), vesico-vaginal fistula (96%) and failure of fistula repair (14%) [68]. This situation is only the tip of an iceberg as not all women concerned could be reached by the awareness campaigns.…”
Section: Findings In Drcmentioning
confidence: 99%